1997
DOI: 10.1136/fn.76.3.f185
|View full text |Cite
|
Sign up to set email alerts
|

Renal calcification in preterm infants: follow up at 4-5 years

Abstract: Aim-To determine the consequences of renal calcification in preterm infants. Methods-A cohort of 11 preterm babies was studied at the age of 4 to 5 years. They had had renal calcification as neonates. Seventeen matched controls were also studied. Each child had a renal ultrasound scan, a calcium load test, and a desmopressin test for renal concentrating ability (RCA). The study group also had glomerular filtration rate (GFR) estimated, using the height:creatinine ratio, and tubular phosphate reabsorption, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
2
10

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 36 publications
1
43
2
10
Order By: Relevance
“…34 If renal damage, such as calcifications, was overt early after birth, then reduced renal function persisted. 35 Two studies of subjects born with LBW, with and without further indication of SGA, found normal renal function at the age of 20 to 30 years. 36,37 Very convincing evidence for the long-term impact of LBW on kidney survival was given in an epidemiological study that showed an increased risk of developing chronic kidney disease stage 5 in those adults born as growthrestricted children.…”
Section: Discussionmentioning
confidence: 99%
“…34 If renal damage, such as calcifications, was overt early after birth, then reduced renal function persisted. 35 Two studies of subjects born with LBW, with and without further indication of SGA, found normal renal function at the age of 20 to 30 years. 36,37 Very convincing evidence for the long-term impact of LBW on kidney survival was given in an epidemiological study that showed an increased risk of developing chronic kidney disease stage 5 in those adults born as growthrestricted children.…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al studied 11 former preterms when they were aged 4-5 years with neonatal NC. They found low median TmP/GFR (tubular maximum of phosphate reabsorption corrected for glomerular filtration rate) in comparison with reference values [71]. Likewise, Saarela et al observed a significantly higher urine β 2 -microglobulin/creatinine ratio in 20 children with NC than in 20 children without NC as preterm neonates, when they were a mean age of 4.7 years.…”
Section: Proximal Tubular Functionmentioning
confidence: 93%
“…On the other hand, two studies demonstrated early morning urine osmolality to be significantly lower in former preterms than in healthy children [6,71]. However, test results indicating impaired concentrating ability after desmopressin was found in 4/30 children with neonatal NC at 1 year and in 2/25 at 2 years [70].…”
Section: Distal Tubular Functionmentioning
confidence: 95%
See 2 more Smart Citations